Alley-Cropping Combinations for the Southeastern USA - Sarah W. Workman; Samuel C. Allen; Shibu Jose (EDIS, 2003)
This paper will provide readers with enough information to plan for alley-cropping on their land. It will describe several examples of alley cropping systems being developed in Florida. Also included is more specific information on the benefits and concerns that accompany this land use system as well as key design factors. Landowners interested in implementing alley-cropping practices should talk to their county extension and forestry professionals about the specific crops and markets that are appropriate for their location. This document, FOR 106, is one of a series through the Center for Subtropical Agroforestry (CSTAF), School of Forest Resources and Conservation, Institute of Food and Agricultural Sciences, University of Florida. First published August 2003.